Peranan Konsep Diri Terhadap Motivasi Berprestasi Pada Siswa RSBI dan Siswa Reguler - Aryanti, Zusy (P3M STAIN Jurai Siwo Metro, 2012)
AbstractNot quarantee RSBI students have good achievement in academic and be succes people if they do not have motivation in it. Achievement motivation is one factor to hold academic achievement that can be influenced by student self concept.The purpose of this study was to examine the relation between self concept and achievement motivation. How percentage self concept role emerge achievement motivation.Â Â Â Â Â Â Â Â Â Â Â The result of this study is founded significant correlation between self concept and achievement motivation. 13,3% self concept play role in RSBI studentsâ achievement motivation and 35,4% in Reguler studentsâ achievement motivation. In other, there is differences between RSBI studentsâ self concept and Reguler studentsâ self concept. Despite there is no differences achievement motivation between RSBI and reguler students.Key Word: self concept, motivation